The promotion of reading in the initial training teacher: considerations for its implementation at the university of Cienfuegos - Torres Calzadilla, Zaydelys Lucrecia; López Rodríguez del Rey, María Magdalena; Martínez Iglesias, Marisol Isabel (Revista Universidad de Guayaquil, 2017)
Reading is one of the most developing practices that man has counted on throughout life. The promotion and encouragement of this habit, from community spaces, reshapes its values and commits those responsible for this type of intervention. The experience developed by a group of professors and students from the University of Science Education in Cienfuegos confirm the formative nature of this practice, which becomes a professional commitment to be legitimized by the didactics that endorses the process of promotion and encouragement of reading in the communities that make up its frame of pedagogical influences
Keywords: reading; pedagogical influences; community spaces; to promote reading; to encourage reading